2006
DOI: 10.1007/s00125-006-0426-x
|View full text |Cite
|
Sign up to set email alerts
|

Lower levels of plasma 25-hydroxyvitamin D among young adults at diagnosis of autoimmune type 1 diabetes compared with control subjects: results from the nationwide Diabetes Incidence Study in Sweden (DISS)

Abstract: Aims/hypothesis Low plasma vitamin D concentrations may promote the development of type 1 diabetes. To test this hypothesis, we measured plasma 25-hydroxyvitamin D (25OHD) in young adults with type 1 diabetes. Methods The nationwide Diabetes Incidence Study in Sweden (DISS) covers 15-to 34-year-old people with newly diagnosed diabetes. Blood samples at diagnosis were collected during the 2-year period 1987/1988. Patients with islet antibodies (islet cell antibodies, GAD antibodies or tyrosine phosphatase-like … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

17
152
5
5

Year Published

2007
2007
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 241 publications
(184 citation statements)
references
References 43 publications
17
152
5
5
Order By: Relevance
“…In our study 25(OH)D was significantly lower (mean ±SD of 7.88 ± 1.20 ng/mL) in patients, compared with 16.64 ± 7.83 ng/mL in the controls. Many recently published studies have found significantly lower levels of 25(OH)D in patients with diabetes compared with controls (6,8,10,26).…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…In our study 25(OH)D was significantly lower (mean ±SD of 7.88 ± 1.20 ng/mL) in patients, compared with 16.64 ± 7.83 ng/mL in the controls. Many recently published studies have found significantly lower levels of 25(OH)D in patients with diabetes compared with controls (6,8,10,26).…”
Section: Discussionmentioning
confidence: 96%
“…Prevalence varied from as high as 90.60% with a vitamin D cutoff value of < 30 ng/ mL in Qatar (6), to as low as 15% with a vitamin D cutoff value of < 20 ng/mL at Joslin's diabetes center (9), and intermediate prevalence of 54% with a vitamin D cutoff value of < 32 ng/mL in DIASS study (8). In one north Indian study, 58% children with T1DM aged between 6 and 12 year were vitamin D-deficient as compared with only 32% in the control group (25).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several observational studies indicate associations between vitamin D deficiency and disorders of the immune system, such as multiple sclerosis, 33 type 1 diabetes, 34 rheumatoid arthritis 35 and rejection of solid organ allografts. 36 Some studies have also shown beneficial effects of vitamin D supplementation, most notably in the prevention of type 1 diabetes, 37 and amelioration of symptoms of multiple sclerosis by treatment with high dose vitamin D. 38 However, the relevance of these findings is questioned due to the lack of prospective, randomized trials.…”
Section: Discussionmentioning
confidence: 99%
“…Both laboratory and clinical studies have provided evidence that vitamin D deficiency is an important environmental factor that can increase the prevalence of certain autoimmune diseases, such as MS [55][56][57] , Crohn disease [58] , diabetes mellitus [59,60] , systemic lupus erythematosus (SLE) [61,62] , asthma [63] , RA [64] , Sjögren's syndrome, systemic vasculitis and antiphospholipid syndrome [65] . A correlation between reduced intake of vitamin D and prevalence of the diseases can be found, which raises the possibility that serum vitamin D level is important for the pathogenesis of autoimmune diseases.…”
Section: Functionsmentioning
confidence: 99%